GGNBP2 regulates histone ubiquitination and methylation in spermatogenesis - Kaimin Guo; Yin Cao; Zhiyi Zhao; Jiantao Zhao; Lingyun Liu; Hongliang Wang (Epigenetics)
Gametogenetin binding protein 2 (GGNBP2) was indispensable in normal spermatids for transformation into mature spermatozoa in mice, and when Gametogenetin binding protein 2 is bound to BRCC36 and RAD51, the complex participates in repairing DNA double-strand breaks (DSB) during the meiotic progression of spermatocytes. Ggnbp2 knockout resulted in the up-regulation of H2AK119ubi and down-regulation of H2BK120ubi in GC-2 cells (mouse spermatogonia-derived cell line) and postnatal day 18 testis lysate. Our results also demonstrated that Gametogenetin binding protein 2 inducedASXL1 to activate the deubiquitinating enzyme BAP1 in deubiquitinating H2A, while Gametogenetin binding protein 2 knockout disrupted the interaction between ASXL1 and BAP1, resulting in BAP1 localization change. Furthermore, the Gametogenetin binding protein 2 deletion reduced H2B ubiquitination by affecting E2 enzymes and E3 ligase binding. Gametogenetin binding protein 2 regulated H2A and H2B ubiquitination levels and controlled H3K27 and H3K79 methylation by PRC2 subunits and histone H3K79 methyltransferase. Altogether, our results suggest that Ggnbp2 knockout increased DNA damage response by promoting H2A ubiquitination and H3K27trimethylation (H3K27me3) and reduced nucleosome stability by decreasing H2B ubiquitination and H3K79 dimethylation (H3K79me2), revealing new mechanisms of epigenetic phenomenon during spermatogenesis. Gametogenetin binding protein 2 seems critical in regulating histone modification and chromatin structure in spermatogenesis.